2022
DOI: 10.1016/j.invent.2021.100493
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and effectiveness of a self-guided mobile app platform for college student mental health

Abstract: Background College students endorse high rates of mental health problems. While many colleges offer on-campus services, many students who could benefit from mental health services do not receive care. Indeed, nearly half of students who screen positive for depression, for example, do not receive treatment. Digital mental health programs, such as those delivered via mobile apps, may help expand access to mental health care and resources. This mixed-methods study aims to examine the uptake and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…While many colleges offer on-campus services, many students who could benefit from mental health services do not receive car. Indeed, nearly half of students who screen positive for depression, for example, do not receive treatment ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…While many colleges offer on-campus services, many students who could benefit from mental health services do not receive car. Indeed, nearly half of students who screen positive for depression, for example, do not receive treatment ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study examined Black male college students’ needs and preferences for using social media and mobile-based apps for their mental health symptoms, stress management, and self-care. This qualitative study stemmed from a larger study [ 51 ] aimed at examining the uptake of a mental health app on 2 university campuses. In line with previous research indicating that minority students underuse existing mental health resources [ 24 , 55 ], early data indicated that Black male students were not enrolling in the parent study or downloading the stress management app despite its wide availability.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings should also be interpreted in consideration of the COVID-19 situation at the time. Given that the study was conducted during the peak of the COVID-19 pandemic, when college students were overwhelmed by a sudden transition to digital and computer-enabled classes and communications, the findings may potentially be influenced by their digital fatigue [ 51 ]. Participants’ perception of using web-based resources and digital tools may also be altered because of this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations